Feminisme revisited - A. Ribberink (BMGN: Low Countries Historical Review, 2000)
R. Oldenziel, C. Bouw, Schoon genoeg. Huisvrouwen en huishoudtechnologie in Nederland 1898-1998; H. Pott-Buter, K.G. Tijdens, Vrouwen. Leven en werk in de twintigste eeuw; G. Blauwhof, Van passie tot professie. Vrouwelijke vliegers in de Nederlandse luchtvaart; N. Manneke, Vrouwen van kaliber. Politievrouwen in de twintigste eeuw; R. van Daalen, M. Gijswijt-Hofstra, Gezond en wel. Vrouwen en de zorg voor gezondheid in de twintigste eeuw; J. Poelstra, Vrouwen aan het Spaarne. Op zoek naar nieuwe wegen; M. Grever, B. Waaldijk, Feministische openbaarheid. De nationale tentoonstelling van vrouwenarbeid in 1898; K. Kruisheer, De dokter, dat ben ik! 65 Jaar Vereniging van Nederlandse vrouwelijke artsen Feminism revisited The extent to which women's and gender history has been integrated in contemporary political history can be described as being 'fairly positive'. This trend can be stimulated by the further development of the discipline of women's and gender history. As far as this is concerned, 1998 proved to a fruitful year in that a huge number of publications were published. Most of them were brought out to commemorate the anniversary of the 1898 National Exhibition of Women's Labour. Eight of these recent books are discussed in this paper. In this literature, the importance of the first and second feminist movements is stressed. During the first feminist wave (1860- 1920) and the period preceding the second feminist wave (1920-1970) the predominant opinion in the Netherlands was that of 'difference', that is the belief that differences between the sexes are more important than similarities. During the second feminist wave (1970-1990), at least in the beginning, this view was curtailed and the opposite view, which stressed the similarities between the sexes, began to prevail.